Analisis Fasilitas Kerja, Lingkungan Kerja Dan Insentif Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Pt. Leaders World Di Gunung Putri Kabupaten Bogor - Haris Adiki; Suyanto Suyanto (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This research aims to analyze the influence of work facilities, work environment, and incentives on employee performance, with work motivation serving as an intervening variable at PT. Leaders World, Bogor. The methodology employed a census of the entire employee population through cluster sampling, with data analysis conducted using multiple linear regression and the Sobel Test. The findings indicate that work facilities and incentives exert a significant positive influence on motivation; however, the work environment does not demonstrate a similar effect. Furthermore, incentives and work motivation were proven to directly bolster performance, whereas the work environment was found to have a negative impact on employee performance. Work motivation was also found to be incapable of mediating the influence of the work environment on performance, suggesting that productivity increases are more heavily dependent on reward-based aspects. Consequently, the company is advised to prioritize the provision of incentives and the fulfillment of facilities to achieve more effective organizational sustainability